Numerical results for polarized light scattering in a spherical atmosphere. (September 2022) - Korkin, S.; Yang, E.-S.; Spurr, R.; Emde, C.; Zhai, P.; Krotkov, N.; Vasilkov, A.; Lyapustin, A.
Highlights: We report numerical results for light reflection from the top of a Rayleigh scattering spherical atmosphere over a dark surface. We account for polarization of light and height-dependent single scattering albedo. We report single and multiple scattering data separately to support validation and development of RT codes for spherical atmospheres. Abstract: We report numerical results for polarized light reflection from the top of a Rayleigh scattering spherical atmosphere with height-dependent single scattering albedo over a dark surface. Michael Mishchenko considered this scenario back in the 1990's, for a plane-parallel atmosphere of unit optical thickness (OT = 1), for which radiance errors arising from neglecting polarization reaches their highest values. To further extend Mishchenko's results, we consider a value of OT = 0.25, for which the effect of atmospheric curvature is pronounced. New results are generated using three state-of-the art radiative transfer (RT) codes. These are: the MYSTIC and MCSSA models, which simulate light scattering in a true-spherical atmosphere using Monte Carlo methods; and the discrete ordinate code VLIDORT, operating with a new multiple-scatter spherical correction designed to deliver reasonable approximations to spherical-medium scattering. In this work, we report results for both single and multiple scattering; this will help to support the validation of existing and future polarized spherical RT codes, especially those using approximative methods to deal with sphericity.